Environmental Governance and Climate Change Adaptation in Indonesia - Novita, Asti Amelia (Jurnal Ilmiah Administrasi Publik, 2021)
This paper examines environmental governance in climate change adaptation efforts in Indonesia. Climate Change has been a common concern, especially since the signing of 194 countries in the Paris Agreement. Climate change adaptation is one of the points in the Paris Agreement as an effort to implement commitments to tackle global climate change. Climate change adaptation is one of the responses made by humans in facing climate change in addition to mitigation. Adaptation is carried out to reduce vulnerability to the effects of climate change. The Indonesian government has made various climate change adaptation efforts, including preparing national policy documents such as INDC, RAN-API, and related regulations to address the impacts of climate change. However, the research results show that strengthening climate change adaptation efforts needs to be balanced with commitment from sharing parties, strengthening the role of the private sector, and proper budget planning. Committees here are associated with the alignment of central and regional policies and the compliance of local governments in implementing climate change adaptation policies. The private sector's role emphasized the contribution of activities and finance to climate change adaptation efforts through corporate social responsibility programs.